(untitled) (Conference Zone, 2022)
Erythematosus is a chronic skin disease characterized by severe itching, characterized by an overflow of monomorphic papules unrelated to acute inflammation. The cause of the disease is not well defined. Many scientists also believe that the occurrence of the disease is related to the disruption of the nervous system.